Can ice cores reveal past events of East Antarctic ice sheet retreat? - Ilaria Crotti; Barbara Stenni; Amaelle Landais; Aurélien Quiquet; Massimo Frezzotti; David Wilson; Mirko Severi; Carlo Barbante (INSTANT2023, 2023)
Ice cores drilled in near-coastal areas of Antarctica could potentially record past margin retreats during previous interglacial periods. The chronology of the TALDICE ice core (159°11’ E, 72°49’S, 2315m a.s.l), drilled in a peripheral area of the East Antarctic Plateau, has recently been extended back to 343,000 years BP (Crotti et al., 2021). The high-resolution isotopic records contained in the deeper and strongly-thinned sections of this ice core reveal unique double-peak features during the late Pleistocene interglacials MIS 7.5 and 9.3, as previously observed for MIS 5.5 in the same core (Masson-Delmotte et al., 2011) and not present in the inland ice core records. Through a combination of glaciological evidence, an offshore Wilkes Subglacial Basin sediment core record (Wilson et al., 2018), and GRISLI ice sheet modelling experiments (Quiquet et al., 2018), we provide an interpretation of this peculiar record. Our results indicate that the interglacial double-peak δ18Oice signal could reflect Talos Dome site elevation decreases during the late stages of interglacials due to ice retreat in the Wilkes Subglacial Basin. These changes coincided with warmer Southern Ocean temperatures and elevated global mean sea level, confirming the sensitivity of the Wilkes Subglacial Basin ice sheet to ocean warming and its potential contribution to sea-level change. References: Crotti, I. et al. An extension of the TALDICE ice core age scale reaching back to MIS 10.1.Quat. Sci. Rev. 266, 107078 (2021). Masson Delmotte, V. et al. A comparison of the present and last interglacial periods in six Antarctic ice cores. Clim 7, 397–423 (2011). Quiquet, A., et al. The GRISLI ice sheet model (version 2. 0): calibration and validation for multi-millennial changes of the Antarctic ice sheet. Geosci. Model Dev. 11, 5003–5025 (2018). Wilson, D. J. et al. Ice loss from the East Antarctic Ice Sheet during late Pleistocene interglacials. Nature 561, 383–386 (2018).